Clinical and molecular characterization of both methicillin-resistant andsensitive staphylococcus aureus mastitis - OREIB, A.; KHALIFA, H.; EID, A.; AHMED, A.; SHIMAMOTO, T.; SHIMAMOTO, T. (Journal of the Hellenic Veterinary Medical Society, 2019)
This study targeted bovine mastitis as a possible source of livestock-associated methicillin-resistant Staphylococcus aureus (MRSA), to identify clinical signs associated with MRSA- and non-MRSA-associated mastitis. Thirty-eight mastitis cases (68 infected quarters) were investigated. Gram-positive cocci-shaped isolates were selected based on Baird Parker agar growth as well as Gram-stained bacterial smears. Molecular screening for Staphylococcus aureus (S. aureus) yielded 17 isolates, of which five (29.41%) were methicillin resistant. The five isolates were mecA positive, but mecC negative. Multilocus sequence typing (MLST) indicated that sequence type 1 (ST1) was the identified type of all isolates of MRSA. S. aureus-associated cases showed different clinical forms of mastitis, including subclinical, acute, chronic, and gangrenous. Additionally, subclinical mastitis was the only detected condition associated with MRSA, which may represent a potential hidden risk for humans. Phenotypically, isolates of MRSA showed resistance to all of the tested β-lactam antimicrobials, with marked resistance to tetracycline and gentamycin. Based on our knowledge, this is the first report to identify MRSA ST1 in Egypt. Bovine mastitis could be a source for the dissemination of MRSA to humans and other animals. Additionally, while methicillin-resistance may have no effect on the clinical outcome of mastitis, it does affect therapeutic success, particularly when β-lactam antimicrobials are used.